On Mapping Satisfying the SC Condition - Bautista, Luzvinminda; Canoy, Sergio Jr. (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This study introduces a certain property that is satisfied by some functions. We show that this property is weaker than that of a weak continuous surjection. Since weak continuity is weaker than continuity, this property is weaker than that of continuous surjection. We shall show that under certain conditions this, and the interiority condition preserve local connectedness.